INFLUENCE OF SOIL PH AND SALINITY ON ELECTRICAL AND DIELECTRIC PROPERTIES (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the influence of soil pH and salinity on the electrical and dielectric properties of soils. By analysing a range of soil samples, we found that soil pH and salinity significantly affect electrical conductivity (EC) and dielectric constant. The correlation analysis revealed a strong inverse relationship between pH and EC, with acidic soils (pH < 6) exhibiting higher EC compared to alkaline soils (pH > 7). Salinity was positively correlated with the dielectric constant, showing that higher salinity levels result in increased dielectric properties. Multiple regression models indicated that EC decreases with increasing pH and increases with higher salinity, while the dielectric constant is positively influenced by both salinity and soil moisture content. Sensitivity analysis further highlighted that pH has a more pronounced effect on EC than salinity. These findings underscore the importance of managing soil pH and salinity to optimize soil health and improve agricultural practices. Understanding these relationships helps in enhancing soil monitoring techniques and precision agriculture strategies, particularly in areas facing challenges from soil salinization and pH imbalances. The results offer valuable insights for developing effective soil management practices to ensure sustainable agricultural productivity and environmental protection.